Analisis Faktor-Faktor Keberhasilan dan Kegagalan Program P3TGAI di Kabupaten Bulukumba - Ezra Artahsasta (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
The Acceleration Program for Irrigation Water Use Improvement (P3TGAI) in Bulukumba Regency is implemented across five sub-districts and involves 11 Community Facilitators (TPM), 22 Irrigation Areas (D.I.), and 22 Water User Farmer Associations (P3A). This study aims to analyze the determinants of success, inhibiting factors, and improvement strategies for program implementation. A quantitative descriptive design was applied to 78 respondents comprising 11 TPMs, 22 P3A chairpersons, 44 beneficiary farmers, and one Management Consultant Assistant. Data were collected through questionnaires, interviews, observations, and document review, and were analyzed using means, index scores, interregional comparisons, and thematic analysis. The results show that all five success factors were categorized as very high. Inter-party communication obtained the highest index of 95.80, followed by work planning at 91.60 and project monitoring at 88.80. The main inhibiting factors were poor communication with the community, with an index of 93.50, and inadequate funding transparency, with an index of 90.20. Higher constraints were identified in Herlang and Kajang due to difficult access and uneven administrative readiness among P3As. Recommended strategies include digitalizing communication and reporting, providing financial administration training for P3As, accelerating location designation, and supporting transportation for facilitators in hard-to-reach areas.